Association Between Work Conditions and Smoking in South Korea - Cho, Young-Seung (2013)
BACKGROUND: A variety of sociodemographic factors, such as gender, age, household income, and educational level, influence individuals' likelihood of smoking. Work-related factors may also be linked to smoking behavior. We sought to investigate the relationship between smoking and work environment in South Korea. METHODS: We analyzed data from the Fifth Korean National Health and Nutrition Examination Survey to determine whether there was an association between smoking and occupation type (e.g., manual, nonmanual, or service work), night-shift work, and hours worked/week (e.g., <40, 40–48, 49–60, or >60 hours) for 4,685 workers. Regression models were adjusted for sociodemographic variables such as age, recent alcohol consumption, hours slept, educational level, and household income. RESULTS: The prevalence of smoking was 50.1% in men and 7.2% in women. For women, manual workers had 2.34 times [95% confidence interval (CI): 1.02–5.36] greater odds of smoking compared with nonmanual workers, whereas service workers had 2.37 times greater odds (95% CI: 1.28–4.40). Furthermore, women who worked 49–60 hours had 2.21 times greater odds of smoking (95% CI: 1.10–3.75) as compared with women who worked 40–48 hours. CONCLUSION: Women who work long hours or who are employed in service or manual positions are more likely to smoke. These results indicate a need in South Korea to target these specific groups when creating nonsmoking policies.